Comparative study on thin-walled structures with function graded strength and tapered angle. Issue 3 (4th May 2019) - Dai, Minghua; Ying, Liang; Ma, Haolin; Chen, Shuai; Hu, Ping
ABSTRACT: This paper compares the crashworthiness characteristics of straight functionally graded strength (SFGS), tapered uniform strength (TUS) and classical straight uniform strength (SUS) tubes under axial crushing loading. Based on the numerical simulation, multi-optimisations are performed to optimise the crashworthiness of the SFGS, TUS and SUS tubes. Result of comparative study shows that the SFGS tubes are similar to the TUS tubes to some extent, since both of them have obviously larger CFE value, relatively good comprehensive crashworthiness and more predominant Pareto fronts than the traditional SUS tubes. Nevertheless, obvious differences between SFGS and TUS tubes exist. The relative differences of SEA and PCF for all the SFGS tubes are positive while that of the TUS tubes are negative. Finally, the comparison on Pareto fronts suggests that if the allowable tapered angle is big enough, it is better to employ the TUS tubes with relatively big tapered angle.